2012
DOI: 10.1124/jpet.111.191239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fasudil, a Selective Inhibitor of Rho Kinase Activity, in the Secondary Injury Associated with the Experimental Model of Spinal Cord Trauma

Abstract: Rho kinase (ROK) may play an important role in regulating the biological events of cells, including proliferation, differentiation, and survival/death. Blockade of ROK promotes axonal regeneration and neuron survival in vivo and in vitro, thereby exhibiting potential clinical applications in spinal cord damage and stroke. The aim of this experimental study was to determine the role of ROK signaling pathways in the inflammatory response, in particular in the secondary injury associated with the experimental mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 53 publications
1
16
0
2
Order By: Relevance
“…Further, SCI promoted the assembly and activity of this inflammasome complex, and neuronal purinergic P2X receptor subtypes are involved in SCI-mediated NALP1 activation [6]. Another report showed that the inhibition of Rho kinase signaling pathways after SCI reduced the secondary neural injury in conjunction with attenuated inflammasome activation [43]. In a recent study, we could demonstrate that polyunsaturated fatty acids such as omega-3 fish oil components are neuroprotective agents in another acute brain damaging model, i.e., ischemic stroke in rats [19].…”
Section: Discussionmentioning
confidence: 96%
“…Further, SCI promoted the assembly and activity of this inflammasome complex, and neuronal purinergic P2X receptor subtypes are involved in SCI-mediated NALP1 activation [6]. Another report showed that the inhibition of Rho kinase signaling pathways after SCI reduced the secondary neural injury in conjunction with attenuated inflammasome activation [43]. In a recent study, we could demonstrate that polyunsaturated fatty acids such as omega-3 fish oil components are neuroprotective agents in another acute brain damaging model, i.e., ischemic stroke in rats [19].…”
Section: Discussionmentioning
confidence: 96%
“…Herein, 3 NP-induced ROCK activation was significantly suppressed following fasudil and simvastatin administration. Beforehand, experimental spinal cord injury was associated with increase in ROCK activity which was markedly attenuated by fasudil treatment [48]. It is worthy to note that the potent ROCK inhibition by fasudil could be mediated via competition for ATP binding site in the ROCK catalytic domain [49].…”
Section: Discussionmentioning
confidence: 99%
“…25 Vários fármacos inibem a apoptose por diversos mecanismos, entre os quais a inibição das caspases, 25 a inibição de diversas vias de sinalização intracelular 26,27 e a redução do estresse oxidativo. 28 Um vasto grupo de fármacos inibe a calpaína, uma endoprotease que promove a apoptose em vários tipos de células através da proteólise de proteínas do citoesqueleto, da membrana e da mielina. 29…”
Section: Inibidores Da Apoptoseunclassified